INTERLANGUAGE IN SOUND: SYLLABLE-STRUCTURE MODIFICATION IN ENGLISH PRONUNCIATION AMONG INDONESIAN PESANTREN LEARNERS - Dian Fajrina Mubarokah; Faiz Rizki Muhammad; Dinar Dipta; Haida Umiera Hashim (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
This study investigates syllable-structure modification in the English pronunciation of 11th-grade students at one of pesantrens institution in East Java. It aims to identify modification types in monosyllabic, disyllabic, and trisyllabic words, determine the most frequently affected syllable positions (onset, nucleus, and coda), and examine these modifications from a Second Language Acquisition (SLA) perspective. Using a descriptive qualitative design, data were collected through pronunciation tasks and semi-structured interviews. The findings show that pronunciation modification occurs systematically, reflecting learners’ developing interlanguage phonology. Four major modification types were identified: substitution, epenthesis, deletion, and cluster reduction. Substitution was the most dominant type, while nucleus modification occurred most frequently, indicating persistent difficulty in vowel production. From an SLA perspective, these patterns are influenced by first-language transfer, phonotactic constraints, and learners’ tendency to assimilate unfamiliar English sounds into existing phonological categories. Increased modification in longer words also suggests the role of cognitive processing limitations. Despite substantial English exposure in the pesantren environment, the persistence of these patterns indicates that input alone is insufficient without explicit phonological awareness and corrective feedback. This study highlights the importance of integrating phonological instruction with SLA-informed approaches to support pronunciation development in EFL contexts.